Fenomena stunting di Indonesia dan tantangan human resource development (HRD) - Chandra Sagul Haratua; Rais Al Azizi Muhyidin; Marco; Malik Akbar Gaung Azaning Jagat (Lancar Media Komunikasi, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term, resulting in impaired growth in children. Stunting is also one of the causes of stunted children's height, so that it is lower than children of their age. Indonesia is a country with a high stunting rate, according to WHO data, Indonesia's prevalence of stunting ranks third in the Southeast Asian region. The phenomenon of stunting has a considerable influence on the quality of human resources in Indonesia in the future.This study uses a qualitative descriptive research method which can be useful for developing a deeper study of Management science that focuses on the realm of human resources (HR). With a demographic bonus, stunting is still one of the problems that must be resolved in order to build a golden generation in 2045. Conditions like this, and the high rate of stunting in Indonesia will present challenges for Human Resources Development (HRD) in recruiting new job candidates. To develop the ability of these prospective workers to be able to compete with others, one way is to conduct training for prospective workers who have these deficiencies to train their skills and knowledge.